Biointerface Coatings for Biomaterials and Biomedical Applications - Chen, Hsien-Yeh; Wang, Peng-Yuan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This succinct reprint provides students and researchers the latest studies to the world of surface coatings in biomedical applications. This eBook contains one editorial, one review paper, and 10 research papers. The technology covers vapor phase coating, wet chemistry coating, and plasma spray. The research areas focus on antifouling, anti-corrosion, and tissue engineering. This specific and accessible reprint is the ideal example of surface coatings for students in bioengineering and materials science.